THE USE OF INSTAGRAM APPLICATION IN LEARNING ENGLISH AT ELEVENTH GRADE STUDENTS OF SMAN 1 BENGKULU TENGAH - Rice Lawita Ikhsan; Fetriani (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The objective of this study was to investigate the use of Instagram application in learning English at eleventh grade students of SMAN 1 Bengkulu Tengah. This study applied a quantitative method. The subject of this research was twenty eight students who learn English at XI MIPA 1 in SMAN 1 Bengkulu Tengah. The researcher used English test to know the use of instagram in teaching English. The English test consisted of four skills of English; listening, reading, speaking, and writing skill. The test was given after the researcher implemented instagram as media in teaching English. Moreover, the researcher made video recording while conducting the research. the use of Instagram application was effective to develop students’ English ability. It was proved by mostly the students got English score >KKM (78) afer using Instagram application. There were only ten students who cannot reach the KKM but their score was still above 60. Moreover, based on the interview result the students’ admitted that the use of Instagram in teaching English was so fun because they can learn while playing. In Instagram there were many accounts which helped them to learn vocabulary, grammar, and four English skills. the researcher recommends the students to apply kind of activities on the Instagram such as making English video or writing the English captions to develop their English skill. Keywords: Learning English, Instagram Application